Принципи роботи в команді як основа її ефективності - Філіппов, В. В. (ХНУРЕ, 2021)
Today’s teams are different from the teams of the past: They’re far more diverse, dispersed, digital, and dynamic (with frequent changes in membership). But while teams face new hurdles, their success still hinges on a core set of fundamentals for group collaboration. The trouble is, effective collaboration is much easier said than achieved. And there are oh so many way ways for it to go wrong. A lot of times, it just doesn’t work. Yet for some reason, how it’s done in practice is rarely talked about. There simply aren’t enough resources dedicated to helping teams get it right. And getting it right is urgently important
Keywords: філософія; принципи роботи в команді